Iron metabolism patterns in non-anemic patients with myasthenia gravis: a cross-sectional and follow-up study - Li, K; Hou, L; Tan, Y; Huang, Y; Shi, J; Han, J; Yan, J; Guan, Y (Frontiers Media, 2022)
Background and purpose: Iron metabolism in myasthenia gravis (MG) and factors associated with it are explored by few published studies. Therefore, this study aimed to compare iron metabolism patterns between patients with MG and healthy individuals as well as between the same group of patients before and after immunotherapy, and to identify predictors of iron metabolism disorders in MG.